Principles of electric circuits : conventional current version - Floyd, Thomas L. (Boston, Massachusetts : Prentice-Hall, 2010)
In this ninth edition, the book continue to provide a complete and straightforward coverage of the basics of electrical components and circuits. Fundamental circuit laws and analysis methods are explained and applied in a variety of basic circuits.
Quantities and units -- Voltage, current, and resistance -- Ohm's law -- Energy and power -- Series circuits -- Parallel circuits -- Series-Parallel circuits -- Circuit theorems and conversions -- Branch, loop, and node analyses -- Magnetism and electromagnetism -- Introduction to alternating current and voltage -- Capacitors -- Inductors -- Transformers -- RC circuits -- RL circuits -- RLC circuits and resonance -- Passive filters -- Circuit theorems in AC analysis -- Time response of reactive circuits -- Three-phase systems in power applications.
Includes index.
Keywords: ELECTRIC CIRCUITS